Sequence and structural insights of monoleucine-based sorting motifs contained within the cytoplasmic domains of basolateral proteins - Harmych, Sarah J.; Tydings, Claiborne W.; Meiler, Jens; Singh, Bhuminder (Frontiers in Cell and Developmental Biology, 2024)
Delivery to the correct membrane domain in polarized epithelial cells is a critical regulatory mechanism for transmembrane proteins. The trafficking of these proteins is directed by short amino acid sequences known as sorting motifs. In six basolaterally-localized proteins lacking the canonical tyrosine-and dileucine-based basolateral sorting motifs, a monoleucine-based sorting motif has been identified. This review will discuss these proteins with an identified monoleucine-based sorting motif, their conserved structural features, as well as the future directions of study for this non-canonical basolateral sorting motif.